Band gap modification and photoluminescence enhancement of graphene nanoribbon filled single-walled carbon nanotubes. Issue 6 (25th January 2018) - Chernov, A. I.; Fedotov, P. V.; Lim, H. E.; Miyata, Y.; Liu, Z.; Sato, K.; Suenaga, K.; Shinohara, H.; Obraztsova, E. D.
Abstract : Graphene nanoribbon formation inside single-walled carbon nanotubes leads to selective photoluminescence enhancement for exact nanotube geometries and depends on the interplay of several factors. Abstract : Molecule encapsulation inside the single-walled carbon nanotube (SWCNT) core has been demonstrated to be a successful route for the modification of nanotube properties. SWCNT diameter-dependent filling results in band gap modification together with the enhancement of photoluminescence quantum yield. However, the interaction between the inner structure and the outer shell is complex. It depends on the orientation of the molecules inside, the geometry of the host nanotube and on several other mechanisms determining the resulting properties of the hybrid nanosystem. In this work we study the influence of encapsulated graphene nanoribbons on the optical properties of the host single-walled carbon nanotubes. The interplay of strain and dielectric screening caused by the internal environment of the nanotube affects its band gap. The photoluminescence of the filled nanotubes becomes enhanced when the graphene nanoribbons are polymerized inside the SWCNTs at low temperatures. We show a gradual photoluminescence quenching together with a selective signal enhancement for exact nanotube geometries, specifically (14, 6) and (13, 8) species. A precise adjustment of the optical properties and an enhancement of the photoluminescence quantum yield upon filling for nanotubes with specific diameters were assigned to optimal organization of the inner structures.